Off season - Siddons, Anne Rivers (New York : Grand Central Pub., 2008)
"Anne Rivers Siddons tells the beautiful, tragic, and redemptive story of a woman who searches for meaning after her husband dies"--Provided by publisher.
Keywords: Widows -- Fiction; Self-realization in women -- Fiction; Psychological fiction